Corporate Governance Practices and Performance of County Government of Narok; Kenya - Ole Shankil, Joshua Kinyamal; Munga, Jane (Human Resource and Leadership Journal, 2025)
Purpose: The main aim of this study was to examine the influence of Corporate Governance Practices on Performance of the County Government of Narok; Kenya. Methodology: This study applied descriptive survey research design. The study used a structured questionnaire on collection of primary data from the County Government of Narok; Kenya. Pilot study was done on the neighboring County Government of Kajiado; Kenya, hence this enabled the testing for reliability and validity of the research instrument. The study descriptive and inferential statistics was analyzed by use of SPSS software, further; a regression equation model was developed to test the relationships between the variables. Findings: The results of the findings indicated Corporate Governance Practices influenced Performance of the County Government of Narok; Kenya. In terms of influence significance; Board Size Practices had more influence on Performance, followed by Board Composition Practices, Chief Executive Officer Duality Practices and Board Skills Level Practices. Unique Contribution to Theory Practice and Policy: The study recommends for County Governments to embrace the use of Corporate Governance Practices since it improves the Performance. The study recommends for further studies on the same considering same variables but different methodologies.